2019
DOI: 10.1242/bio.043570
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of HE4 suppresses aggressive cell growth and malignant progression of ovarian cancer by inhibiting the JAK/STAT3 pathway

Abstract: Human epididymis protein 4 (HE4) is well known to be a predictor of ovarian cancer clinically. HE4 is reported to play crucial roles in ovarian cancer progression and metastasis. The purpose of the present study was to explore its biological role and molecular mechanism in ovarian cancer. In our study, we found that expression levels of HE4 in tissues, serum and urine in ovarian cancer were upregulated compared to healthy and benign groups. HE4 expression was elevated in ovarian cancer cells. Knockdown of HE4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
(34 reference statements)
1
22
0
1
Order By: Relevance
“…In recent years, a growing number of investigations have gradually found that HE4 promotes cell proliferation, adhesion, invasion, migration, and chemoresistance in ovarian cancer [20][21][22][23][24][25][26][42][43][44][45][46][47]. It was found that HE4 overexpression or rHE4 treatment in EOC cells resulted in upregulation of many transcripts coding for extracellular matrix proteins, including LAMC2, LAMB3, SERPINB2 and GREM1; moreover, in cells overexpressing HE4 or exposed to rHE4 in culture medium, the protein levels of LAMC2 and LAMB3 were continously increased, and in the presence of bronectin, the focal adhesions were elevated in cells treated with rHE4 [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a growing number of investigations have gradually found that HE4 promotes cell proliferation, adhesion, invasion, migration, and chemoresistance in ovarian cancer [20][21][22][23][24][25][26][42][43][44][45][46][47]. It was found that HE4 overexpression or rHE4 treatment in EOC cells resulted in upregulation of many transcripts coding for extracellular matrix proteins, including LAMC2, LAMB3, SERPINB2 and GREM1; moreover, in cells overexpressing HE4 or exposed to rHE4 in culture medium, the protein levels of LAMC2 and LAMB3 were continously increased, and in the presence of bronectin, the focal adhesions were elevated in cells treated with rHE4 [22].…”
Section: Discussionmentioning
confidence: 99%
“…It was known that ovarian cancer participates in evading immunosurveillance and orchestrating a suppressive immune microenvironment, a series of studies by James NE, et al [23,44,45] found that, upon exposure of puri ed human peripheral blood mononuclear cells(PBMCs) to HE4, osteopontin (OPN) and DUSP6 appeared as the most inhibited and upregulated genes; the proliferation of human ovarian carcinoma cells in conditioned media from HE4-exposed PBMCs was enhanced, while the effect was attenuated by adding recombinant OPN or OPN-inducible cytokines (IL-12 and IFN-γ); HE4 can compromise both OPN-mediated T cell activation [44] and cytotoxic CD8 + /CD56 + cells through upregulation of self-produced DUSP6 [45], thus promoting the tumorigenesis of ovarian cancer [23,44,45,48]. Other researchers found that HE4 promotes carcinogenesis of ovarian cancer by combining with histone deacetylase 3 (HDAC3) to activate PI3K/AKT pathway [46], and that HE4 knockdown suppresses the invasive cell growth and malignant progress of ovarian cancer by inhibiting JAK/STAT3 pathway [24]. Until now, a few studies have begun to delineate HE4's role in chemoresistance of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing number of studies have shown that HE4 promotes the proliferation, adhesion, invasion, migration, and chemoresistance in ovarian cancer cells [20][21][22][23][24][25][26][42][43][44][45][46][47]. HE4 overexpression in, or recombinant HE4 treatment of, EOC cells resulted in the upregulation of many transcripts coding for extracellular matrix proteins, including LAMC2, LAMB3, SERPINB2, and GREM1; moreover, in cells overexpressing HE4 or those exposed to recombinant HE4 in the culture medium, the protein levels of LAMC2 and LAMB3 were observed to continuously increase.…”
Section: Discussionmentioning
confidence: 99%
“…Further, HE4 may regulate the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase/AKT signal transduction (PI3K/AKT) pathways to exert tumor-suppressive effects in vitro [18,19]. Recently, studies have been carried out to investigate the association between HE4 and tumorigenesis as well as chemotherapeutic resistance in EOC; however, these have shown inconsistent results [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%